Christian Friendship: John, Paul, and the Philippians - Fitzgerald, John J. (Interpretation, 2007)
Both John and Paul ground friendship in love, yet their conceptions differ in important ways. This article provides a brief discussion and comparison of their two understandings and concludes with a treatment of Paul's use of friendship language in Philippians.